The impact of autonomous driving in the trucking ecosystem - Sousa, Francisco Ribeiro Ferreira Guedes De (2021)
Autonomous trucks have a great potential to be the first transport application of autonomous driving in the U.S., due to easier road navigation, operational benefits and a driver shortage. As trucking is the dominant mode of freight transportation in the country, the full adoption of autonomous trucks could save $87.57billion in driver wages per year and create an excess fleet situation, with 2.36 million trucks at risk to become obsolete. This would have implications for the value chain stakeholders, specifically drivers, owner-operators, OEMs and suppliers, creating new business models and a different freight distribution network.